Neuronal activity in the primate hippocampal formation during a conditional association task based on the subject's location - Eifuku, S; Nishijo, H; Kita, T; Ono, T (The Journal of neuroscience, 1995)
The hippocampal formation (HF) functions in two domains of memory: spatial and nonspatial associative memory. The HF includes the hippocampus proper, the dentate gyrus, and the subicular complex. Studies of spatial correlates of HF neuronal activity have revealed that a subject's location in space can impose critical constraints on patterns of neuronal activity in the HF. This report compares monkey HF neuronal responses in two kinds of stimulus-response association tasks (go/no-go tasks with symmetrical reinforcement). In a place-dependent, conditional, stimulus-response association (PCA) task, the subject's location was the condition upon which stimulus (object)-behavioral response association depended. In a place-in-dependent, simple, stimulus-response association (ISA) task, the object-behavioral response contingency was independent of the subject's location. Of 329 neurons recorded, the activity of 88 increased or decreased significantly in response to the presentation of an object during the PCA task. Responses of 17 neurons depended differentially on specific combinations of object, place, and behavior in the PCA task (specific- combination neurons). These specific-combination responses do not simply reflect object-behavioral response association in the PCA task, since neuronal responses in the same object-behavioral response association were not restored in the ISA task in which there was no dependence on the subject's location. This suggests the influence of location on HF neuronal responses in object-behavioral response association when the subject's location is imposed as a condition. Responses of 12 neurons differentiated the kind of object in the PCA task (object-differential neurons). In the ISA task, most object- differential responses diminished or disappeared. Since the HF object- differential responses elicited by the conditions imposed by the PCA task. Characteristics of the two neuron types suggest that HF neurons encode both stimulus percept and attributes such as the place where the stimulus is presented and the conditional relation imposed in the task.